Julgamento parcial de mérito e o novo código de processo civil - Smolka, Marcela Ferrauche (2017)
This monograph was presented in march 2017 for the conclusion of the Lato Sensu Postgraduate Course - Specialization in Civil Procedural Law, at the Pontifical Catholic University of São Paulo, under the orientation of Prof. Dr. Rogério Licastro Torres de Mello. For the development of the study that is proposed, in the first moment, will be analysed the principiological basis that motivated the insertion of the technique of fractionation of judgment in the new Civil Procedure Code. Also in the first part, to contextualize the theme and to reach the comprehension of the technique to its full extent, will be held an assertive approach on the concept of merit, the evolution of the conceptualization of sentence and interlocutory decision, as well as considerations will be drawn about the chapters of the sentence, depth of judge's cognitive activity and hypothesis of joinder of claims. Drafted the conceptual and principiological framework, the second part of the study will focus specifically on the technique of partial judgments on the merits, covering topics such as its legal nature and origin, analyzing, in this area, the institutes existents in the Civil Procedure Code of 1973 that already demonstrated the possibility of fractionation of judgments, as well as the issue of the end of the dogma from Giuseppe Chiovenda about the “unità e unicitá della decisione”. In this second part of the paper, a necessary approach will also be made about its requirements and hypotheses. After that, will be faced the practicals and technicals challenges of applying the institute, and also the consequences of the partial judgment of merit from a perspective of the context brought by the New Civil Procedure Code. Its reflexes in the appeals system, in the res judicata, in the execution phase and in the counting of the peremptive period for the filing of the rescissory action. Finally, some paragraphs will be drawn up as a conclusion and will be listed the doctrinal works and articles used as the basis and inspiration for the study